Innovation in Basic Education Administration in the Digital Technology Era - Pumnuch, Thatthanun; Pansiri, Wannaree; Chotientip, Tasanee (Suan Dusit Graduate School Academic Journal, 2025)
The purpose of this academic paper was to focus on the study of appropriate administrative methods by studying and analyzing the concept of innovation in basic education administration in the digital technology era, and explore guidelines to promote innovation in basic education administration in the digital technology era. This was in line with the Office of the Basic Education Commission’s strategy to create quality output in accordance with the framework. Nowadays, new innovations have changed people’s lives in the world, and technology has been continuously developed until a variety of inventions have emerged. The results of the analysis showed that digital technology was important for educational administration to be able to connect to the Internet network for data storage, data sharing on Cloud system, communication, appointment scheduling, job assignment and sending meeting minutes through online system. In this academic paper, the author presented guidelines to promote innovation in basic education administration, which was an important process in the development of the education system. If an organization developed innovations that utilized its resources to benefit or increase productivity to the agency, it would be able to innovate agency management. It was used as a guideline for the development of innovations in basic education management in the digital technology era that had a positive impact on society and the nation for further advancement.